(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Engineers all over the world have been trying to find out workable solutions to keep project time over-run under good control. The activitynetworking technique initiated in the USA in the late fifties gained large popularity. This was followed by the introduction of the computer and a large number of management softwareaiming ateffective project control. The techniques arein use globally including in the developing world. Needless to saythese techniques have proved veryuseful, but the real problem of effectively controlling the slippage on construction projects, particularlyin the developing countries, still remains largelyunsolved. The author has done substantial work in India and otherdeveloping countries trying to find workable solutions to this burning issueand have achieved somesuccess. Keeping in view this experience, the author has been actively pursuing further studies, researchand detailed work in this area and his broad findings are outlined in this paper.